Teacher readiness for online learning: Scale development and teacher perceptions - Hung, Min-Ling (Computers and education, 2016)
The purpose of this research is to examine elementary and middle school teachers' readiness as online learners on the basis of the Teacher Readiness for Online Learning Measure (TROLM). This paper draws on three years (spring 2012–spring 2014) of data from an online course on Internet literacy and ethics for practicing teachers. Two sets of samples (128 and 248 teachers) facilitated this study's exploration and confirmation of the TROLM model's constructs. Results of exploratory and confirmatory factory analysis support an 18-item scale comprising four factors: communication self-efficacy, institutional support, self-directed learning, and learning-transfer self-efficacy. This study found that male teachers exhibited statistically significantly greater readiness in the dimension of learning-transfer self-efficacy than did female teachers. Teachers with a master's degree assigned a heavier weight to the dimensions of communication self-efficacy and learning-transfer self-efficacy than did teachers with a bachelor's degree. This study made two additional findings: the fewer teaching years a teacher had, the higher the teacher's communication self-efficacy tended to be; and the more teaching years a teacher had, the higher the teacher's self-directed learning tended to be. Suggestions for further research are provided. •This study explores four main factors.•This study examines elementary and middle school teachers' readiness as online learners.•Male teachers exhibited greater readiness in learning-transfer self-efficacy.•The fewer teaching years a teacher had, the higher the teacher's communication self-efficacy tended to be.